2022
DOI: 10.1037/ocp0000285
|View full text |Cite
|
Sign up to set email alerts
|

The role of recovery for morning cognitive appraisal of work demands: A diary study.

Abstract: We examined the role of daily recovery for morning cognitive appraisal of work demands in a daily diary study. We predicted that psychological detachment from work during the evening would be associated with changes in cognitive appraisal from afternoon to the next morning. Additionally, we predicted that these associations are mediated by state of being recovered in the morning. We collected data from 183 employees with 3 daily measurement occasions over 2 consecutive workweeks. We analyzed the data using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Based on our findings, this future research should delve deeper into the processes by which modifying somatic conditions (e.g., appropriate clothes, sleep, and fresh air) fosters job performance. For instance, having slept sufficiently might lead employees to have more energy (Weigelt & Prem, 2021 ) and to perceive their work as less demanding (e.g., Casper & Wehrt, 2021 ), thus being better able to perform well. But why does modifying somatic conditions foster job performance more effectively than changing physical or social conditions?…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, this future research should delve deeper into the processes by which modifying somatic conditions (e.g., appropriate clothes, sleep, and fresh air) fosters job performance. For instance, having slept sufficiently might lead employees to have more energy (Weigelt & Prem, 2021 ) and to perceive their work as less demanding (e.g., Casper & Wehrt, 2021 ), thus being better able to perform well. But why does modifying somatic conditions foster job performance more effectively than changing physical or social conditions?…”
Section: Discussionmentioning
confidence: 99%
“…Related to this temporal aspect, research has traditionally examined work events and experiences that have already happened. Increasing evidence, however, suggests that also the anticipation of events and experiences can have an impact on well‐being (Rosen et al., 2020) and that well‐being states may influence anticipation processes (Casper & Wehrt, 2022). Accordingly, future studies will need to investigate the joint impact of anticipated and experienced workplace factors on health and well‐being, along with potential reverse effects.…”
Section: Limitations Of Past Research and Directions For Future Researchmentioning
confidence: 99%
“…Past research has demonstrated that recovery experiences are important for employees’ well-being (Headrick et al, 2023; Sonnentag et al, 2022). For instance, recovery experiences have been examined with respect to breaks at work (e.g., Bennett et al, 2020; Sianoja et al, 2018), off-job time during evenings (e.g., Casper & Wehrt, 2022; S. L. Parker et al, 2020), and weekends (e.g., Binnewies et al, 2010; Fritz et al, 2010).…”
Section: The Recovery Processmentioning
confidence: 99%